(untitled) (Colombia Medica, 1987)
Through the transvaginal route (anterior and posterior colpotomy), 130 ligatures of fallopian tubes were made over four years. The surgeries were performed without the patient’s hospitalization. The most common method was posterior colpotomy (61.5%), allowing a straightforward approach to the tubes. The anterior colpotomy was used when other pathology (cystocele, rectocele) was present. Post-operative complications were minimal (1.5%) when compared with other techniques. The sterility rate of the method was 99.2%, and its acceptance by the patients was excellent.